Information technology duty, satisfaction and ais effectiveness moderate effect of benefits of informs technology on employee performance - Astika , Ida Bagus Putra; Dwirandra , AANB (International research journal of management, IT and social sciences, 2020)
The purpose of this study was to determine the effect of IT benefits on employee performance. The specific objective of this study was to determine the effect of moderation in IT-task suitability, satisfaction, and effectiveness of AIS on the effect of IT usefulness on employee performance. The study population and using a purposive sampling method to determine the research sample. Furthermore, primary data was collected using a modified questionnaire from previous researchers and tested the validity and reliability of the instrument. Then, the collected data is tabulated and analyzed using MRA analysis techniques, through the following stages: 1) classical assumption test for compliance with the Best Linear Unbiased Estimator (BLUE) requirements which include: normality test, heteroscedasticity test, and multicollinearity test, 2) model feasibility test (F test), 3) analysis of the coefficient of determination (Adj. R2), and 4) hypothesis testing (t-test). The results showed that the usefulness of IT had a significant positive effect on employee performance. IT-task suitability, AIS satisfaction, and AIS effectiveness reinforce the positive influence of AIS benefits on employee performance.